2019
DOI: 10.3847/1538-4357/ab33fe
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Lag for a Radiating Jet Shell with a High-energy Cutoff Radiation Spectrum

Abstract: Recent research shows that the spectral lag is closely related to the spectral evolution in GRBs. In this paper, we study the spectral lag for a radiating jet shell with a high-energy cut-off radiation spectrum. For the jet shell with a cut-off power-law spectrum, the spectral lag monotonically increases with the photon energy and levels off at a certain photon energy. It is the same for the jet shell with a Band cut-off spectrum (Bandcut). However, a turn-over from the positive lags to negative lags appears i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…Although there are numerous mechanisms to explain this [see e.g. [6][7][8][9][10][11][12], this behaviour is qualitatively the same as for a massive photon or a QG theory with ξ = +1 and could thus provide evidence for such theories.…”
Section: Introductionmentioning
confidence: 77%
“…Although there are numerous mechanisms to explain this [see e.g. [6][7][8][9][10][11][12], this behaviour is qualitatively the same as for a massive photon or a QG theory with ξ = +1 and could thus provide evidence for such theories.…”
Section: Introductionmentioning
confidence: 77%
“…We find that our weakest constraint is for the time delay between the highest and lowest energy channels ((i, j) = (4, 1)), where we find ∆γ 41 < 3.4 × 10 −15 at 1σ confidence. This is unsurprising because each pulse of a GRB's lightcurve is known to peak first at higher energy due to spectral evolution [47][48][49][50], although the reasons for this are not fully understood [20][21][22][23][24][25][26]. This results in the majority of observed time delays obeying ∆t ij > 0 for i > j, so one expects the largest time delay for this pair and hence the weakest constraint.…”
Section: Resultsmentioning
confidence: 99%
“…The physical mechanisms which result in the GRB spectral lag are unknown; the search for the nature of spectral lag is an ongoing research topic where most of the focus lies on investigating possible effects at the source [see e.g. [20][21][22][23][24][25][26]]. It has for example been shown that the effects of spectral lag can be recreated from simple source models utilising rapid bulk acceleration on relativistic jet shells [26].…”
Section: Observational Datamentioning
confidence: 99%
“…Ref. [64] has found a correlation between spectral and spectral evolution. We shall explore other models for intrinsic emission and their impact on LIV searches in the forthcoming sections.…”
Section: Model Used For Time Lagsmentioning
confidence: 95%